Pendidikan Tauhid Pada Anak Dalam Perspektif Hadis - Ubay Dillah; Repa Hudan Lisalam (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
The idea of ​​monotheism education for children at an early age is to make children love Allah SWT more, there is nothing to fear except Allah SWT, to emphasize children in worshiping Him, and to guide children to always be grateful for all the blessings that Allah SWT has given. Tawheed education in children is intended to increase spiritual potential and shape children's character so that they become human beings who believe and are devoted to God Almighty and have noble character. The method used is hadith thematic with a qualitative approach. The results of this research show that instilling the concept of monotheism education in early childhood is very important, because the most important thing is to introduce monotheism. Monotheism is the foundation for every Muslim. If a person is truly monotheistic then he will gain salvation in this world and the hereafter, however, without monotheism he will definitely fall into shirk and will face retribution in this world and retribution in the afterlife. And in view of the hadith, monotheism is highly recommended for children starting from childhood, so that the child knows his creator